The Role of the Microbiome in the Developmental Origins of Health and Disease - Stiemsma, Leah T; Michels, Karin B (Pediatrics (Evanston), 2018)
Although the prominent role of the microbiome in human health has been established, the early-life microbiome is now being recognized as a major influence on long-term human health and development. Variations in the composition and functional potential of the early-life microbiome are the result of lifestyle factors, such as mode of birth, breastfeeding, diet, and antibiotic usage. In addition, variations in the composition of the early-life microbiome have been associated with specific disease outcomes, such as asthma, obesity, and neurodevelopmental disorders. This points toward this bacterial consortium as a mediator between early lifestyle factors and health and disease. In addition, variations in the microbial intrauterine environment may predispose neonates to specific health outcomes later in life. A role of the microbiome in the Developmental Origins of Health and Disease is supported in this collective research. Highlighting the early-life critical window of susceptibility associated with microbiome development, we discuss infant microbial colonization, beginning with the maternal-to-fetal exchange of microbes in utero and up through the influence of breastfeeding in the first year of life. In addition, we review the available disease-specific evidence pointing toward the microbiome as a mechanistic mediator in the Developmental Origins of Health and Disease.